The Curriculum Administration of Music Classroom Program in Secondary School, under the Office of the Basic Education Commission - Tammapheechaya, Piriyapong; Malaitao, Thararat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were 1) to study the curriculum administration of the music classroom project in secondary schools under the office of the basic education commission, 2) to compare the curriculum administration of the music classroom project in secondary schools classified by the size of the educational institution. The samples used in research were obtained from a specific randomized sample, from the population of 20 participating schools, namely school director, school deputy director, curriculum committee, music classroom project leader, art subject group leader, and music teacher. A sample group was 300 people. The tool used was a 5-level estimation scale model based on the Likert model, 50 items. The confidence value of the questionnaire was equal to 0.941. The statistics used to analyze the data were percentage, mean, standard deviation, and t-test. The results showed that 1) The curriculum administration of the music classroom project in secondary schools, under the office of the basic education commission in all 5 aspects found that the overall level was at a high level (mean=4.30, SD=0.45), and when considering each aspect found that all aspects of curriculum administration were at a high level, the aspect with the highest average was the aspect of the preparation of educational institutions (mean=4.35, SD=0.48), followed by the aspect of curriculum development into practice. (mean=4.31, SD=0.47), the curriculum administration assessment (mean=4.30, SD=0.49), curriculum consistency (mean=4.28, SD=0.48), respectively; The aspect with the lowest average was curriculum supervision (mean=4.26, SD=0.50). 2) The results of a comparative analysis of the curriculum administration of the music classroom program in secondary schools, under the office of the basic education commission, classified by school sizes, found that extra-large schools and large schools had overall curriculum administration, and each aspect was statistically significant different at the .01 level.